Development of Multi-dimensional Scale to Measure the Abilities of Rural Women towards Entrepreneurship - Tripathy, Maitreyee; Bishnupriya Mishra,; Guru Prasad Satapathy, (Indian Journal of Extension Education, 2024)
ABSTRACTEntrepreneurship has emerged as a powerful tool for rural women's empowerment, offering them opportunities to generate income, build self-confidence, and transform their lives. By engaging in entrepreneurial activities, rural women can leverage their skills, creativity, and local knowledge to establish and manage businesses that address the unique needs and challenges of their communities. The present study aimed to develop and validate a multi-dimensional scale for evaluating rural women's entrepreneurial skills, essential for empowering communities through the establishment of small businesses promoting economic progress. The study was conducted in 2023. 60 attitudinal items were initially gathered, evaluated for relevance, and examined. The scale's final composition included 41 statements spread across six sub-dimensions viz. Cognitive skill, Motivational skill, Social & Relational skill, Management skill, Technical skill and Strategic skill. Cronbach's Alpha was used to assess reliability, and the resultant coefficient of 0.81 was satisfactory. Expert evaluation was used to check the validity of the content. Researchers in relevant fields can use this standardized scale to evaluate rural women's entrepreneurial abilities, either as is or with adjustments, promoting empowerment and community development.